Effect of temperatures and loading rates on direct shear strength of asphaltic concrete using layer-parallel direct shear test - Lung, C. K.; M. R., Mohd Hasan; M. O., Hamzah; A., Sani; S., Poovaneshvaran; Putra Jaya, Ramadhansyah (IOP Publishing, 2020)
This paper evaluates the influence of temperatures and loading rates on the shear strength of dense asphalt (AC14) prepared based on the Malaysian Public Works Department specification. In this study, different specimen conditioning temperatures, 10°C, 20°C, 30°C, and loading rates of 20.88mm/min, 40.88mm/min, 50.88mm/min, and 60.8mm/min were used to assess the performance of specimens by using Layer-Parallel Direct Shear (LPDS) test. Based on the results, both parameters have significant effects on the shear strength of the asphalt specimens. The results indicate that the loading rate is directly proportional to the shear strength of asphalt specimens. It is because the stiffness of the asphalt mix increases as the loading rate increases. Hence, it enhanced the shear strength of asphalt specimens. On the other hand, the temperature is inversely proportional to the shear strength of asphalt mixes. As the temperature increases, the stiffness of the asphalt mixture reduces due to the lower resilient modulus; therefore, it reduces the shear strength of the specimen.